Core-shell nanoreactor as well as preparation method and application thereof
By covering the SIO2 shell on the ZIF-67 surface, the MN-ZIF-67 nuclear and SIO2 shell core reactor is prepared, which solves the problem of poor MOFS nuclear stability and low catalytic activity, and achieves high catalytic activity and high stability Sexual catalysts are suitable for catalytic ozone oxidation reactions.
Patent Information
- Application Number
- CN202411484052.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
The stability of MOFs cores in the prior art is poor, which limits its durability and reliability in various application scenarios. At the same time, there are still technical challenges in improving the catalytic activity of MOFs.
By covering the silicon shell on the surface of the metal organic skeleton material ZIF-67, the MN-ZIF-67 core and the SiO2 shell are prepared. And high -temperature burn technology to prepare the catalyst.
It achieves high catalytic activity and stability of the catalyst, avoids direct contact between the active sites and the external environment, increases the service life of the catalyst, and reduces the risk of metal leaching.
Smart Images

Figure CN119346130A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental nano materials, and in particular relates to a core-shell nanoreactor and a preparation method and application thereof. Background Art
[0002] Antibiotics remaining in the environment will aggravate the contamination of pathogenic microorganisms, lead to hidden dangers in drinking water safety, and endanger human health. In recent years, the excessive use and disorderly discharge of tetracycline antibiotics have had a continuous adverse impact on ecological balance and human health. How to conveniently and effectively deal with this type of "emerging pollutants" has become one of the research hotspots in the field of environment. Ozone catalytic oxidation technology has a strong ability to degrade organic pollutants and is not easy to produce secondary pollution. These significant advantages make it widely used in the field of sewage treatment. Among them, homogeneous ozone catalytic oxidation technology has obvious defects such as low ozone utilization rate and difficulty in separating the catalyst from the wastewater after treatment. The heterogeneous ozone catalytic oxidation technology uses porous materials to prepare carriers, loads metal oxides as active components to prepare solid catalysts that are easy to recycle and reuse, and can make up for some of the defects of homogeneous ozone catalytic oxidation technology. Therefore, the performance of the catalyst plays a decisive role in the efficiency of catalytic ozone oxidation reaction.
[0003] In the past few decades, core-shell nanostructures have become the focus of researchers due to their excellent physicochemical properties and unique morphology. Compared with pure core structures, core-shell structures can exhibit new chemical, biological or catalytic activities. The type of core and shell materials is the most important factor in determining the performance of the final core-shell structure. The core can be composed of a variety of materials. In addition to traditional metal nanoparticles, oxides and semiconductor materials that can be used as the core, some new materials can also be used as the core to prepare core-shell materials, such as MOFs, COFs, etc. There is a significant shortcoming in the existing technology in using MOFs as core materials, that is, the stability of the MOFs core is poor. This defect limits the durability and reliability of MOFs in various application scenarios. In addition, although MOFs have shown great potential in the field of catalysis, there are still technical challenges in improving the catalytic activity of MOFs. At the same time, there are also technical bottlenecks in expanding the application of MOFs materials in more fields. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a core-shell nanoreactor with high catalytic activity and high stability; another purpose of the present invention is to provide a preparation method and application of the core-shell nanoreactor.
[0005] Technical solution: The core-shell nanoreactor of the present invention comprises a Mn-ZIF-67 core and a SiO2-coated Mn-ZIF-67 core. 2 shell.
[0006] Preferably, the Mn-ZIF-67 core and SiO 2 The mass ratio of the shell is 6:1 to 7:1.
[0007] Further preferably, the Mn-ZIF-67 core and SiO 2 The mass ratio of the shell is 6.8:1.
[0008] The method for preparing the core-shell nanoreactor of the present invention comprises the following steps:
[0009] Step 1: Add a mixed solution of manganese acetylacetonate, ethanol and water to the ZIF-67 dispersion, stir until the mixture is uniform, add a mixed solution of TEOS and ethanol and stir for 6 to 8 hours to obtain Mn-ZIF-67@SiO 2 Solution;
[0010] Step 2: Mn-ZIF-67@SiO 2 The solution was centrifuged and dried to obtain Mn-ZIF-67@SiO 2 Solid powder;
[0011] Step 3: Mn-ZIF-67@SiO 2 The solid powder is carbonized to obtain a hollow core-shell nanoreactor.
[0012] Preferably, in step 1, the mass ratio of ZIF-67 to manganese acetylacetonate is 7:1 to 8:1, and the mass ratio of TEOS to manganese acetylacetonate is 1:1 to 2:1.
[0013] Further preferably, in step 1, the mass ratio of ZIF-67 to manganese acetylacetonate is 7.1:1, and the mass ratio of TEOS to manganese acetylacetonate is 1.1:1.
[0014] Preferably, in step 1, ZIF-67 is synthesized from 2-methylimidazole and cobalt nitrate, and the dispersion solvent is a mixed solution of p-aminophenol, water and ethanol.
[0015] Preferably, the stirring temperature in step 1 is room temperature.
[0016] Preferably, in step 2, the centrifugal speed is 5000-8000 rpm, and the centrifugal time is 2-5 min; the drying is oven drying, the drying temperature is 50-80° C., and the drying time is 5-8 h.
[0017] Preferably, in step 3, the Mn-ZIF-67@SiO obtained in step 2 is 2 The solid powder is carbonized at 500-700°C in an air atmosphere.
[0018] Preferably, the carbonization heating rate is 3-5°C / min.
[0019] Application of the core-shell nanoreactor of the present invention in catalytic ozone oxidation.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the core-shell nanoreactor of the present invention not only realizes the functional complementarity and morphological optimization of different particles, but also the active sites of the catalyst are wrapped by a porous shell, avoiding direct contact between the active sites and the external environment, thereby improving the service life of the catalyst; under the protection of the shell structure, the overall structure of the catalyst can be made more stable, reducing the risk of metal leaching, and improving the catalytic activity of the catalyst. The preparation method of the core-shell nanoreactor is simple, and it has great application potential in the application of catalytic ozone oxidation degradation of organic pollutants in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a synthetic route diagram of the core-shell nanoreactor of Example 1 of the present invention;
[0022] Figure 2 This is a SEM image of the core-shell nanoreactor of Example 1 of the present invention;
[0023] Figure 3 This is a transmission electron microscopy (TEM) image of the core-shell nanoreactor of Example 1 of the present invention;
[0024] Figure 4 X-ZIF-67@SiO 2 and XRD patterns of core-shell nanoreactor;
[0025] Figure 5 This is the XPS graph of the core-shell nanoreactor before and after use in Example 1 of the present invention;
[0026] Figure 6 This is an experiment of catalytic ozone oxidation degradation of tetracycline in the core-shell nanoreactor of Example 1 of the present invention and Comparative Examples 1 to 4;
[0027] Figure 7 It is the removal rate of the core-shell nanoreactor after 5 cycles in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0029] The present invention uses in-situ growth and high-temperature calcination technology, uses TEOS as a silicon source, dopes transition metal Mn, covers the surface of metal organic framework material ZIF-67 with a silicon shell, and obtains a hollow, porous, and multi-core core-shell nanoreactor through high-temperature calcination. The core-shell nanoreactor prepared by this method has a synergistic catalytic effect of bimetallic doping, is more conducive to the generation of active sites, thereby improving the catalytic performance and service life of the catalyst.
[0030] Example 1
[0031] Step 1, Solution A: 18 g 2-methylimidazole powder was dissolved in 300 mL deionized water and stirred for 15 min to make it completely dispersed; Solution B: 0.3 g p-aminophenol was dissolved in a mixture of 100 mL deionized water and 50 mL ethanol, ultrasonicated to make it completely dispersed, and 1 g cobalt nitrate (Co(NO 3 ) 2 6H 2 O) Stir to dissolve.
[0032] Step 2, pour the mixed solution B obtained in step 1 into the mixed solution A and stir for 10 minutes, add 0.4 g of manganese acetylacetonate and stir for 2 hours, add 1 mL of tetraethyl orthosilicate (TEOS), and stir for 6 hours.
[0033] Step 3: centrifuge the mixed solution obtained in step 2 at 7000 rpm for 3 min, wash it with water and ethanol once, and dry the product obtained by centrifugation in an oven at 60°C for 6 h to obtain Mn-ZIF-67@SiO 2 Purple powder.
[0034] Step 4: Mn-ZIF-67@SiO obtained in step 3 2 The purple powder was calcined in a tubular furnace at 600 °C under air conditions with a heating rate of 5 °C / min for 2 h to obtain a core-shell nanoreactor named YSCMO.
[0035] Figure 1 The synthetic route diagram of the core-shell nanoreactor.
[0036] Example 2
[0037] Step 1, Solution A: Dissolve 15 g of 2-methylimidazole powder in 300 mL of deionized water and stir for 15 min to completely disperse it; Solution B: Dissolve 0.3 g of p-aminophenol in a mixture of 100 mL of deionized water and 45 mL of ethanol, and disperse it completely by ultrasound. Add 1 g of cobalt nitrate (Co(NO 3 ) 2 6H 2 O) Stir to dissolve.
[0038] Step 2, pour the mixed solution B obtained in step 1 into the mixed solution A and stir for 10 minutes, add 0.4 g of manganese acetylacetonate and stir for 2 hours, add 1 mL of tetraethyl orthosilicate (TEOS), and stir for 7 hours.
[0039] Step 3: centrifuge the mixed solution obtained in step 2 at a speed of 5000 rpm for 2 min, wash it with water and ethanol once, and dry the product obtained by centrifugation in an oven at 50°C for 5 h to obtain Mn-ZIF-67@SiO 2 Purple powder.
[0040] Step 4: Mn-ZIF-67@SiO obtained in step 3 2 The purple powder was calcined in a tube furnace at 600 °C under air conditions with a heating rate of 3 °C / min for 2 h to obtain a core-shell nanoreactor named YSCMO.
[0041] Example 3
[0042] Step 1, Solution A: Dissolve 20 g of 2-methylimidazole powder in 300 mL of deionized water and stir for 15 min to completely disperse it; Solution B: Dissolve 0.3 g of p-aminophenol in a mixture of 100 mL of deionized water and 50 mL of ethanol, and disperse it completely by ultrasound. Add 2 g of cobalt nitrate (Co(NO 3 ) 2 6H 2 O) Stir to dissolve.
[0043] Step 2, pour the mixed solution B obtained in step 1 into the mixed solution A and stir for 10 minutes, add 0.4 g of manganese acetylacetonate and stir for 2 hours, add 1 mL of tetraethyl orthosilicate (TEOS), and stir for 8 hours.
[0044] Step 3: The mixed solution obtained in step 2 was centrifuged at 8000 rpm for 5 min, washed once with water and once with ethanol, and the product obtained by centrifugation was dried in an oven at 80 °C for 8 h to obtain Mn-ZIF-67@SiO 2 Purple powder.
[0045] Step 4: Mn-ZIF-67@SiO obtained in step 3 2 The purple powder was calcined in a tube furnace at 600 °C under air conditions with a heating rate of 4 °C / min for 2 h to obtain a core-shell nanoreactor named YSCMO.
[0046] Comparative Example 1
[0047] Step 1, Solution A: 18 g 2-methylimidazole powder was dissolved in 300 mL deionized water and stirred for 15 min to make it completely dispersed; Solution B: 0.3 g p-aminophenol was dissolved in a mixture of 100 mL deionized water and 50 mL ethanol, ultrasonicated to make it completely dispersed, and 1 g cobalt nitrate (Co(NO 3 ) 2 6H 2 O) Stir to dissolve.
[0048] Step 2, pour the mixed solution B obtained in step 1 into the mixed solution A and stir for 10 minutes, add 0.4 g of ferric acetylacetonate and stir for 2 hours, add 1 mL of tetraethyl orthosilicate (TEOS), and stir for 6 hours.
[0049] Step 3: The mixed solution obtained in step 2 was centrifuged at 7000 rpm for 3 min, washed once with water and once with ethanol, and the product obtained by centrifugation was dried in an oven at 60 ° C for 6 h to obtain Fe-ZIF-67@SiO 2 Purple powder.
[0050] Step 4: The YSCM purple powder obtained in step 3 is calcined in a tubular furnace at 600° C. under air conditions with a heating rate of 5° C. / min for 2 h to obtain a YSCFO core-shell nanoreactor.
[0051] Comparative Example 2
[0052] Step 1, Solution A: 18 g 2-methylimidazole powder was dissolved in 300 mL deionized water and stirred for 15 min to make it completely dispersed; Solution B: 0.3 g p-aminophenol was dissolved in a mixture of 100 mL deionized water and 50 mL ethanol, ultrasonicated to make it completely dispersed, and 1 g cobalt nitrate (Co(NO 3 ) 2 6H 2 O) Stir to dissolve.
[0053] Step 2, pour the mixed solution B obtained in step 1 into the mixed solution A and stir for 10 minutes, add 0.3 g of copper acetylacetonate and stir for 2 hours, add 1 mL of tetraethyl orthosilicate (TEOS), and stir for 6 hours.
[0054] Step 3: centrifuge the mixed solution obtained in step 2 at 7000 rpm for 3 min, wash once with water and once with ethanol, and dry the product obtained by centrifugation in an oven at 60°C for 6 h to obtain Cu-ZIF-67@SiO 2 Purple powder.
[0055] Step 4: Cu-ZIF-67@SiO 2 The purple powder was calcined in a tube furnace at 600 °C under air conditions with a heating rate of 5 °C / min for 2 h to obtain a YSCCO core-shell nanoreactor.
[0056] Comparative Example 3
[0057] Step 1, Solution A: 18 g 2-methylimidazole powder was dissolved in 300 mL deionized water and stirred for 15 min to make it completely dispersed; Solution B: 0.3 g p-aminophenol was dissolved in a mixture of 100 mL deionized water and 50 mL ethanol, ultrasonicated to make it completely dispersed, and 1 g cobalt nitrate (Co(NO 3 ) 2 6H 2 O) Stir to dissolve.
[0058] Step 2, pour the mixed solution B obtained in step 1 into the mixed solution A and stir for 10 minutes, add 0.3 g of nickel acetylacetonate and stir for 2 hours, add 1 mL of tetraethyl orthosilicate (TEOS), and stir for 6 hours.
[0059] Step 3: The mixed solution obtained in step 2 was centrifuged at 7000 rpm for 3 min, washed once with water and once with ethanol, and the product obtained by centrifugation was dried in an oven at 60 ° C for 6 h to obtain Ni-ZIF-67@SiO 2 Purple powder.
[0060] Step 4: Ni-ZIF-67@SiO obtained in step 3 2 The purple powder was calcined in a tube furnace at 600°C under air conditions with a heating rate of 5°C / min for 2 h to obtain a YSCNO core-shell nanoreactor.
[0061] Comparative Example 4
[0062] Step 1, Solution A: 18 g 2-methylimidazole powder was dissolved in 300 mL deionized water and stirred for 15 min to make it completely dispersed; Solution B: 0.3 g p-aminophenol was dissolved in a mixture of 100 mL deionized water and 50 mL ethanol, ultrasonicated to make it completely dispersed, and 1 g cobalt nitrate (Co(NO 3 ) 2 6H 2 O) Stir to dissolve.
[0063] Step 2, pour the mixed solution B obtained in step 1 into the mixed solution A and stir for 10 minutes, add 1 mL of tetraethyl orthosilicate (TEOS), and stir for 6 hours.
[0064] Step 3: centrifuge the mixed solution obtained in step 2 at 7000 rpm for 3 min, wash once with water and once with ethanol, and dry the product obtained by centrifugation in an oven at 60°C for 6 h to obtain ZIF-67@SiO 2 Purple powder.
[0065] Step 4: The YSCM purple powder obtained in step 3 was calcined in a tubular furnace at 600° C. under air conditions with a heating rate of 5° C. / min for 2 h to obtain a YSCO core-shell nanoreactor.
[0066] Figure 2 a It can be seen that Mn-ZIF-67@SiO 2 The core-shell nanoreactor material has a clear dodecahedral structure. Figure 2 b It can be seen that the YSCMO material is concave inward, which is due to the high-temperature calcination causing the organic matter to shrink inward. Figure 3 This is the TEM image of the catalyst. It can be seen that YSCMO is a hollow structure covered by a layer of silica shell. There are abundant active sites distributed inside, which can greatly increase its specific surface area.
[0067] X-ray diffraction (XRD) confirmed that Mn-ZIF-67@SiO 2 The crystal structure of Figure 4 a), the 2θ positions of 10.34°, 12.7°, 18.02°, 22.08°, 24.48°, 26.58° and 29.56° belong to the (002), (112), (222), (114), (233), (134) and (044) crystal planes of ZIF-67, respectively. Figure 4 b is the XRD pattern of the YSCXO core-shell nanoreactor obtained after high-temperature calcination. The XRD patterns at 31.20°, 36.88°, 59.20° and 65.19° belong to Co 3 O 4 The (220), (311), (511) and (440) crystal planes belong to the (201) and (210) crystal planes of manganese oxide at 41.17° and 57.23°, respectively, indicating that the YSCMO core-shell nanoreactor was successfully prepared.
[0068] The surface elemental composition and chemical bonding properties of YSCMO were analyzed using X-ray photoelectron spectroscopy (XPS). As shown in the figure, C, O, N, Mn, Co, and Si elements have been clearly identified on the surface of the prepared core-shell nanoreactor. Figure 5 b presents that the C1s XPS spectrum can be divided into three types of peaks at 284.8, 286.0, and 288.5 eV, which are attributed to CC / C═C, CO, and -C═O bonds, respectively. Figure 5 c shows the Co 2p XPS spectrum. The peaks at about 781.9 and 780.4, 795.3 and 797.1 eV correspond to the Co 2p 3 / 2 and Co 2p 1 / 2 and two typical satellite peaks (labeled as “Sat.”, 781.4 eV and 796.9 eV). Figure 5 d shows the Mn 2p XPS spectrum. The Mn 2p spectrum is decomposed into 2p 3 / 2 and 2p 1 / 2 The four spin-orbit peaks.
[0069] The YSCMO core-shell nanoreactor in Example 1 was used to catalyze the ozone oxidation of the organic pollutant tetracycline (TTCH).
[0070] The degradation performance of tetracycline (TTCH) was tested using UV-1800PC UV spectrophotometer from Mepda Instrument Co., Ltd. First, 200 mL of TTCH solution with a concentration of 100 ppm was prepared, 0.15 L / min of ozone was introduced, and 40 mg of the YSCMO core-shell nanoreactor prepared above was added to the TTCH solution as a catalyst. Figure 6 As shown in Figure 2, within 40 minutes, at room temperature, the degradation efficiency of 40 mg of the material for a TTCH solution with an initial concentration of 100 ppm was as high as 94%, and after 5 cycles ( Figure 7 ) after being treated with 1% MgCl2O3 and 1% MgCl2O3, it still has a good degradation effect.
Claims
1. A core-shell nanoreactor, characterized in that: It includes a Mn-ZIF-67 core and a SiO2 shell covering the Mn-ZIF-67 core.
2. The core-shell nanoreactor according to claim 1, characterized in that: The mass ratio of the Mn-ZIF-67 core to the SiO2 shell is 6:1 to 7:
1.
3. A method for preparing the core-shell nanoreactor according to claim 1, characterized in that: The following steps are involved: Step 1, adding a mixed solution of manganese acetylacetonate, ethanol and water to a ZIF-67 dispersion, stirring until the mixture is uniform, adding a mixed solution of TEOS and ethanol and stirring for 6 to 8 hours to obtain a Mn-ZIF-67@SiO2 solution; Step 2, centrifuging and drying the Mn-ZIF-67@SiO2 solution obtained in step 1 to obtain a Mn-ZIF-67@SiO2 solid powder; Step 3, carbonizing the Mn-ZIF-67@SiO2 solid powder obtained in step 2 to obtain a hollow core-shell nanoreactor.
4. The method for preparing the core-shell nanoreactor according to claim 3, characterized in that: In step 1, the mass ratio of ZIF-67 to manganese acetylacetonate is 7:1 to 8:1, and the mass ratio of TEOS to manganese acetylacetonate is 1:1 to 2:
1.
5. The method for preparing the core-shell nanoreactor according to claim 3, characterized in that: In step 1, ZIF-67 is synthesized from 2-methylimidazole and cobalt nitrate, and the dispersion solvent is a mixed solution of p-aminophenol, water and ethanol.
6. The method for preparing the core-shell nanoreactor according to claim 3, characterized in that: The stirring temperature in step 1 is room temperature.
7. The method for preparing the core-shell nanoreactor according to claim 3, characterized in that: In step 2, the centrifugal speed is 5000-8000 rpm, and the centrifugal time is 2-5 min; the drying is oven drying, the drying temperature is 50-80° C., and the drying time is 5-8 h.
8. The method for preparing the core-shell nanoreactor according to claim 3, characterized in that: In step 3, the Mn-ZIF-67@SiO2 solid powder obtained in step 2 is carbonized at 500-700°C in an air atmosphere.
9. The method for preparing the core-shell nanoreactor according to claim 8, characterized in that: The carbonization heating rate is 3-5°C / min.
10. Use of the core-shell nanoreactor according to claim 1 or 2 or the core-shell nanoreactor prepared by any preparation method of claims 3 to 9 in catalytic ozone oxidation.